2019
DOI: 10.4103/jlp.jlp_122_18
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characterization of beta-lactamase-producing Escherichia coli isolates from a tertiary care hospital in India

Abstract: BACKGROUND: The purpose of the study was to determine the prevalence and characterize the resistance profiles of Escherichia coli isolated from various clinical specimens by various phenotypic and genotypic methods. MATERIALS AND METHODS: A total of 196 consecutive, nonduplicate strains of clinically significant E. coli isolated from various clinical specimens were included in the study. Identification and antimicrobial susceptibility testing was performed by using Vitek-2 system (Biomerieux, France)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 25 publications
2
15
2
Order By: Relevance
“…[13][14][15][16][17] Among Escherichia coli, ESBL production was found in 31.05% of the isolates which is lower compared to other similar studies done in India. 17,18 In our study, 16.67% of the Klebsiella isolates were ESBL positive. In comparison, study done in Bangalore showed a higher prevalence of 46.6% among Klebsiella pneumoniae isolates.…”
Section: Discussionmentioning
confidence: 46%
“…[13][14][15][16][17] Among Escherichia coli, ESBL production was found in 31.05% of the isolates which is lower compared to other similar studies done in India. 17,18 In our study, 16.67% of the Klebsiella isolates were ESBL positive. In comparison, study done in Bangalore showed a higher prevalence of 46.6% among Klebsiella pneumoniae isolates.…”
Section: Discussionmentioning
confidence: 46%
“…South-Asia has become the hotbed of antimicrobial resistance, with some studies from India reporting a prevalence ranging from a modest 3% to an extremely high rate of around 65% CREs in clinical isolates [3][4][12][13]. Tigecycline and colistin are used as agents of choice for the treatment of CRE infections but treatment is complicated by uncertainties regarding the efficacy and adverse effects [14].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in urban tertiary care hospitals of Northern Indian states, namely Delhi and Haryana reported a high prevalence of carbapenemase-producing E. coli detected by phenotypic methods as 65.1% and 44%, respectively. [ 29 30 ] However, there are few studies on the magnitude of the problem of CRE carbapenem resistance in the rural population reported from India. A pilot study conducted for a period of 1 year (January–December 2015) by the present laboratory reported lower prevalence of carbapenemase-producing E. coli and K. pneumoniae , i.e., 7.8%[ 9 ] compared to studies from rural Southern India reporting 19.4%–22.1% carbapenemase production among similar isolates.…”
Section: Discussionmentioning
confidence: 99%